ABO blood groups do not predict progression of traumatic intracranial hemorrhage. (August 2021) - Tutunjian, Alyssa M.; Arabian, Sandra S.; Paolino, Jacqueline; Wolfe, Elizabeth S.; Mahoney, Eric J.; Hojman, Horacio M.; Johnson, Benjamin P.; Bugaev, Nikolay
Highlights: The largest study investigating ABO blood groups and bleeding tendency in traumatic intracranial hemorrhage (TICH). Discovered no significant correlation between O and non-O blood groups and radiologic progression of TICH. Hospital course, morbidity, and mortality were not different between O and non-O blood groups. Abstract: ABO blood groups are associated with genetically predisposed variations in von Willebrand factor (VWF) resulting in higher risks of thrombotic events in non-O blood types and bleeding complications in blood type O. The role of ABO blood groups in progression of traumatic intracranial hemorrhage (TICH) is unknown. Given statistically lower VWF levels in blood type O in the general population, we hypothesized that blood type O patients have a higher risk of such progression. A retrospective review of adult trauma patients with isolated TICH admitted to a Level 1 trauma center over eight years was conducted. Patients were categorized with blood type O and non-O (types A, B, AB) delineation. The primary outcome was radiological progression of TICH during the first 24 h. Secondary outcomes included surgical intervention after follow-up computed tomography (CT), complications, days on mechanical ventilation (DMV), intensive care unit (ICU) length of stay (LOS), hospital LOS, and mortality. Of 949 patients, 432 (45.5%) had blood type O. When comparing O and non-O groups, no significant differences were found in gender, age, race, admission vital signs, Glasgow Coma Scale, coagulation profile, TICH type, or Injury Severity Score. No difference in TICH progression was found between O and non-O groups: 73 (17%) vs 80 (15%), respectively, p = 0.55. Blood type O mortality was 12 (3% vs. 23 (4%), p = 0.174). Rate of TICH surgical intervention after follow-up CT, DMV, complications, and ICU and hospital LOS did not differ. No association between ABO blood types and radiological progression of TICH was identified.